Educating faith amid algorithms (a case study of intergenerational relations in urban families of mataram city) - Jepri Utomo; Subhan Abdullah; Prabu Rohman; Suaebah; Lidya Arlini (12 Waiheru, 2025)
This study aims to analyze how urban families in Mataram City educate their children in faith amid the algorithmic era. The research is based on shifts in family education patterns due to the penetration of digital technology, which has displaced parental authority, created communication fragmentation, and challenged the continuity of religion's role in guiding children's learning. A descriptive qualitative approach with a multi-unit case study design was employed. The research involved five urban families in Mataram City, selected purposively based on their active use of digital devices, parental involvement in children's education, and the application of religious values in daily life, all of which were relevant to the study's focus. Data were collected through in-depth interviews, participatory observation, and documentation, and were then analyzed thematically and interactively with methodological and source triangulation to ensure validity. The findings reveal that digital education and religious values complement each other in maintaining intergenerational harmony. First, the shift of educational authority from parents to digital sources is addressed through collaboration between moral values and technology at home. Second, the fragmentation of communication caused by gadget dominance is mitigated by creating moments of togetherness and reflective dialogue among family members. Third, religious values serve as a moral compass that guides the ethical and responsible use of technology. The study concludes that educating faith amid algorithms means integrating technology with spiritual and relational values, rather than rejecting digitalization. These findings underscore the importance of fostering family-based humanistic digital literacy that strikes a balance between technical competence and ethical and spiritual awareness.